Integration of Climate Education in Science Learning to Foster Students' Environmental Awareness - Puspitasari, Ratna (Scientica Education Journal, 2025)
This study examines the integration of climate education in science learning to foster students' environmental awareness through systematic literature review of 27 scientific articles published between 2020-2025, the purpose of the research is to identify effective approaches, strategies, and science learning models in integrating climate education and evaluate its impact on students' environmental awareness, the research method uses systematic literature review with Inclusion Criteria An article that discusses the integration of climate education in science learning, published in the period 2020-2025, and using an empirical approach, the results of the study show that the inquiry-based learning approach, project-based learning, and the integration of technologies such as Augmented Reality and interactive media have proven to be effective in increasing students' understanding and awareness of climate, school-university collaboration through citizen science also has a positive impact For practical learning about climate issues, learning that integrates science, technology, social, and humanities (STEM and E-STEM) aspects shows optimal results in building students' critical awareness, the integration of climate education in science learning not only improves cognitive knowledge, but also develops students' affective aspects and action skills against climate change.